THE RUDISTS OF SOUTHERN ISTRIA - AN EXAMPLE OF ENVIRONMENTALLY INDUCED SUCCESSION WITHIN SANTONIAN LIMESTONES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Rudist bivalves thrived commonly in the shallow carbonate platforms of the Cretaceous Tethyan realm. The presence of two vertically separated Rudist assemblages along two well preserved Upper Cretaceous sections of cape Mrlera (southern part of the Istrian peninsula) is interpreted as environmentally induced faunal replacement. The first succession begins with pelagic limestones, followed by a mixed radiolitid-hippuritid assemblage, and by monogeneric floatstones-biostromes of radioliotids. The lower pelagic unit represents relatively open marine conditions while the uppermost radiolitid unit originated under more restricted marine conditions.Radiolitid floatstones with rare Gorjanovicia bouquets represent the beginning of the second succession. A mixed radiolitid-hippuritid assemblage, characterised by radiolitid floatstones where rare large Vaccinites individuals occur, replaces the radiolitid assemblages in vertical succession. In both sections, sea level changes were the most important factor causing the replacement of rudist assemblages. Slight differences between the two successions could be attributed to differences in submarine topography. Radiolitids and hippuritids might have occupied different biotopes within subtidal environments of the Adriatic carbonate platform. Hippuritids preferred more stable and deeper subtidal environments. By contrast, radiolitids preferred the shallowest parts of subtidal areas. Therefore, these two major rudist groups may be used for determination of different paleoecological conditions.